Boosting Sperm Count Using Red Ginger in Mice Induced by Paraquat Dichloride (1.1-dimethyl-4.4 bipyridinium) - Siti Umairoh; Sutyarso Sutyarso; M. Kanedi; Hendri Busman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Paraquat dichloride (1.1'-dimethyl-4.4'-bipyridinium dichloride) was commonly herbicide used by most farmers in Indonesia. It raises herbicide-free radicals and affects male reproductive organs. It caused infertility such as a decrease in the number of spermatogenic cells. Fortunately, red ginger has capable of dealing with infertility problems. This study aims to see whether the ethanol extract of red ginger can increase the number of spermatocyte and spermatid cells induced by paraquat dichloride. This study uses a completely randomized design with 24 male mice were divided into six treatment groups with four replications. Group K as a control (H2O), J (Ginger 18 mg / ml), Pq (Paraquat 20mg / BB), P1 (Pq 20 mg / BB + EEJM 6 mg / ml), P2 (Paraquat 20mg / BB + EEJM 12 mg / ml) and P3 (Paraquat 20mg / BB + EEJM 18 mg / ml). Paraquat is given 2 times a week for 21 days, while the ethanol extract of red ginger added for 35 days. The number of cells spermatocyte and spermatid cells of male mice and performed analysis of variance (ANOVA) and Least Significant Difference Test (BNT) level of 5% observed as the parameter. The results showed that ethanol extract of red ginger 6, 12 and 18 mg/ml increased the number of spermatocyte and spermatid cells of male mice induced by paraquat dichloride.